Evaluasi Kualitas Kimia dan Fermentabilitas in vitro Isi Rumen Sapi Bali Timor dari Rumah Potong Hewan (RPH) Yang Berbeda - Aploegi, Samson D.; Dami Dato, Twen O.; Hilakore, M. A.; Wie Lawa, Emma D. (Yayasan Sumber Daya Manusia Cerdas, 2025)
This study aims to determine the chemical quality and fermentability of the rumen contents of female Bali Timor cattle in vitro. This research used an experimental method with T-test analysis (comparative test). The number of samples for each was 15 female Timor Bali cattle as replicates, taken from two different slaughterhouses, namely Bimoku abattoir (government-owned) and Aldia Oben abattoir (privately owned). The variables observed were crude protein, crude fiber content, and concentrations of VFA and NH3. The data obtained were analyzed using a T-test (independent sample t-test) at a significance level of 5%, namely comparing the quality of the cattle rumen contents of Bimoku and Oben abbatoir. All data were processed with SPSS 25 software. The statistical analysis results of the t-test showed that the crude protein content and concentration of NH3 of the two locations was not significantly different (P> 0.05), the crude fiber content of Bimoku RPH was significantly higher (P<0.05) than RPH Oben, and VFA concentration from RPH Oben was significantly (P<0.05) higher than Bimoku RPH. It was concluded that differences in abattoir management before slaughtering affected the quality of the rumen contents of female Timor Bali cattle